PERBANDINGAN SOSIAL DAN RASA INSECURE PADA GENERASI Z: STUDI KUALITATIF TERHADAP PENCAPAIAN TEMAN SEBAYA DI ERA DIGITAL - Silvia Mariah Handayani; Sardi Pranata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social comparison has become one of the prominent issues experienced by Generation Z in the digital era. The ease of access to social media enables individuals to observe the achievements of their peers, encouraging them to compare themselves with others. This study aims to analyze the phenomenon of social comparison among Generation Z toward their peers' achievements in the digital era and to understand its impact on individuals. This research employed a qualitative approach with a phenomenological design. The subjects of the study were students of the Faculty of Education, State University of Medan (UNIMED). Data were collected through in-depth interviews with six informants and questionnaires distributed to thirty respondents. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that social media serves as the primary space where social comparison occurs among Generation Z. The most common forms of comparison involve academic achievement, personal skills, productivity, financial conditions, and career accomplishments. Factors contributing to feelings of insecurity include peers' achievements, pressure to succeed at a young age, standards of success promoted on social media, and fear of being left behind by others. The study also reveals that social comparison has dual effects: it can lead to insecurity, low self-confidence, and overthinking, while simultaneously motivating individuals to improve themselves. These findings suggest that the ability to critically interpret information obtained from social media is essential for Generation Z in developing self-confidence and maintaining psychological well-being in the digital era.